A PSYCHOLOGICAL ANALYSIS OF THE NOVEL LAUT BERCERITA BY LEILA S. CHUDORI - I Gusti Nyoman Putra Kamayana; Dewi, Ni Luh Desy Suari (LPPM Universitas Dhyana Pura, 2025)
This study aims to describe the psychology or psyche, especially the emotions of the main character in the novel Laut Bercerita by Leila S. Chudori. The method used is a descriptive method, qualitative, with a behavioristic approach. The data source is the novel Laut Bercerita by Leila S. Chudori, while the data are in the form of words, phrases, sentences, or paragraphs. The data collection technique uses documentary techniques and the data collection tool is the researcher herself as the key instrument who acts as the planner, implementer, analyzer, and interpreter of research data. The results of the data analysis show that the emotions found in the main character are positive emotions and negative emotions. Positive emotions include love and happiness, while negative emotions include anger, hate, fear, and sadness. These emotions can be seen from various events experienced by the main character. Emotions can influence the attitude and character of the main character in the novel Laut Bercerita by Leila S. Chudori. The emotions that dominate in this novel are negative emotions.